2015
DOI: 10.1634/theoncologist.2014-0442
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets in Biliary Carcinogenesis and Implications for Therapy

Abstract: Biliary tract cancers (BTCs) encompass a group of invasive carcinomas, including cholangiocarcinoma (intrahepatic, perihilar, or extrahepatic), and gallbladder carcinoma. Approximately 90% of patients present with advanced, unresectable disease and have a poor prognosis. The latest recommendation is to treat advanced or metastatic disease with gemcitabine and cisplatin, although chemotherapy has recorded modest survival benefits.Comprehension of the molecular basis of biliary carcinogenesis has resulted in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 104 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…Since the prognosis of CCA remains poor with traditional chemotherapy, in the era of personalized medicine several research teams have been working on the molecular and genetic characterization of CCA to identify molecular targets (5)(6)(7)(8)14). Landscape of signalling pathways offers multiple therapeutic targets including growth factor receptors (GFRs) like epidermal (EGFR), vascular (VEGFR), human epidermal growth factor receptor 2 (HER2), the ligand of VEGFR (VEGF) and their downstreaming signal molecules of RAS-RAF-MEK-ERK and PI3K-ACT-mTOR (5)(6)(7)(8)14). Targetspecific monoclonal antibodies and tyrosine kinase inhibitors are able to block selectively the over-expressed or over-activated signal molecules potentiating the growth and invasion of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the prognosis of CCA remains poor with traditional chemotherapy, in the era of personalized medicine several research teams have been working on the molecular and genetic characterization of CCA to identify molecular targets (5)(6)(7)(8)14). Landscape of signalling pathways offers multiple therapeutic targets including growth factor receptors (GFRs) like epidermal (EGFR), vascular (VEGFR), human epidermal growth factor receptor 2 (HER2), the ligand of VEGFR (VEGF) and their downstreaming signal molecules of RAS-RAF-MEK-ERK and PI3K-ACT-mTOR (5)(6)(7)(8)14). Targetspecific monoclonal antibodies and tyrosine kinase inhibitors are able to block selectively the over-expressed or over-activated signal molecules potentiating the growth and invasion of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…In CCA the frequency of BRAF V600E has been reported to range 0-12% in EH and 0-22% in IH subtypes (5)(6)(7)(8)14). Although BRAF V600 can serve as a potential molecular target in CCA, until now there was no evidence of benefit using BRAF inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even amongst those able to undergo radical resection, the recurrence risk is high and the 5-year overall survival is only 30% [3]. One of the first-line chemotherapeutic agents, cisplatin, has been universally found to benefit individuals with advanced, unresectable or metastatic gallbladder cancer [4, 5]. The current standard first-line treatment for unresectable CCA is combination treatment with gemcitabine and cisplatin, however, drug resistance is common and the prognosis of patients is universally poor [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yoshikawa et al reported that the epidermal growth factor receptor overexpression was associated with lymph node metastasis, lymphatic vessel invasion and perineural invasion in extrahepatic CCA, and vascular endothelial growth factor overexpression with intrahepatic metastasis in intrahepatic CCA [ 8 ]. In addition, several studies have indicated that epigenetic modifications of genes involved in progression turned out to be another possible mechanism underlying CCA metastasis [ 9 ]. For instance, E-cadherin promoter methylation was found to be associated with increased migration and invasion in CCA [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%